The Role of Vocational Counseling Programs in the Rehabilitation of the Students with Mental Disability from the perceptions of Counselors and Teachers in Makkah - Alharbi, Rajaa Abdullah (Journal of Educational and Psychological Sciences, 2021)
This study aims to recognizing the Role of Vocational Counseling Programs in the Rehabilitation of the Students with Mental Disability from the perceptions of Counselors and Teachers and applying level of vocational counseling Programs, the most important roles of counselors and teachers in vocational counseling, also aims to recognize the differences between study sample degrees averages due to variable of work nature, the sample of the study consists of fifty three counselor and teacher by using Descriptive Survey Approach, The scale of the study was constructed on the basis of a previously used scale, where it contained 35 paragraphs divided into four dimensions. the study had some results as: arithmetic mean of sample individuals responds on dimensions (Role of Vocational Counseling Programs& applying level of vocational counseling Programs) was middle level, the most important role of counselor and teacher is recommendation that provide to the student due to her abilities, the most important barriers to provide vocational counseling is limited of spatial capacity, the results showed that there are significant statistical differences between vocational counseling degrees averages in the study sample for dimensions (Role of Vocational Counseling Programs& applying level of vocational counseling Programs) due to work nature variable for counselors, the researcher recommended to upgrade the level of Vocational Counseling Programs Application for disabilities female students in rehabilitation schools with cooperation of specialists in this filed, holding courses& seminars, conferences in field of vocational counseling for disabilities students, in addition to perform more od studies and researches about vocational counseling for disabilities in general, and especially for mental disability.
Keywords: Vocational Counseling; Vocational Rehabilitation; Mental Disability; Secondary School